Using Proposed Approach to Solve nonlinear Partial Differential Equations - Hussein, Noor A.; Hani, Najwan Noori (JOURNAL OF ADVANCES IN MATHEMATICS, 2023)
The purpose of this research is to employ a new method to solve nonlinear differential equations to obtain precise analytical solutions and overcome computation challenges without the need to discretize the domain or assume the presence of a small parameter, where the method demonstrated a quick and highly accurate solving nonlinear partial differential equations with initial conditions, in compared to existing methods. The phases of the proposed method are straightforward to implement, highly precise, and quickly converge to the correct result.